Persepsi Mahasiswa UIN Sultan Maulana Hasanuddin Banten Terhadap Label Halal Pada Produk Kosmetik Ms Glow - Fharizal Prakasa Suhaimi; Intan Wulandari; Siti Camila Nurpadillah; Wahyu Hidayat (KOLONI, 2023)
MS Glow is a beauty product that has received a halal certificate for its products. As Muslim consumers, they must be more selective in choosing beauty products that will be used for their daily needs and must comply with Islamic sharia law. This study aims to analyze how the perceptions of students of UIN Sultan Maulana Banten, regarding the halal certification of Ms Glow's cosmetic products. Which uses a quantitative descriptive methodology, to find out how the perceptions of UIN Sultan Maulana Hasanuddin Banten students regarding the halal certification of Ms Glow's cosmetic products. The findings of this study indicate that partially brand image has a positive and significant effect on purchase intention, partially halal label has a positive and significant effect on purchase intention, and partially online customer review has a positive and significant effect on purchase intention, as well as brand image simultaneously. Halal labels, and online customer reviews have a positive and significant effect on the intention to buy MS Glow in students of Uin Sultan Maulana Hasanuddin Banten. Keywords: halal labels, cosmetic products, online customer reviews